Репресії угорської влади проти українського націоналістичного руху в Закарпатті (1939-1944) - Славік, Юрій Володимирович; Slavik, Yuriy V. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті розглянуто діяльність українського націоналістичного руху в Закарпатті в період угорської окупації. Зокрема, проаналізовано внутрішньополітичні передумови для розвитку даного руху, масштаби та основні напрямки його діяльності. Окремо висвітлено репресії проти українського підпілля з боку угорських силових структур.The activity of Ukrainian underground movement in Transcarpathia during the Hungarian occupationis researched in this article. Total repression against Ukrainian political movement in Transcarpathia after the occupation of Carpatho-Ukraine led to its disappearance from the political map of region. A new underground political organization during the Hungarian power was organized by OUN, which ideological platform has found supporters among the transcarpathian youth. In particular, political preconditions for the development of this movement, the scope and main directions of its activity in the region are investigated in this article. Separately repression of the Hungarian law enforcement agencies against the Ukrainian underground are covered; relations of the Hungarian political circles on the existence of the movement in the region was analyzed.
Hungarian repression against Ukrainian nationalist movement in Transcarpathia (1939-1944)
Keywords: Угорщина; репресії; Закарпаття; ОУН; Ковнерівський процес; Hungary; repression; Transcarpathia; OUN; Kovnerovsky process